Assessment of the physical, built and social community environment using Systematic Social Observation: Development of the “Cyprus Neighborhood Observational Tool for urban community environments” - CyNOTes - Kleopa, Daphne (My University, 2023)
There are several community assessment methods, all with advantages and disadvantages. For example, while census-based indicators of socio-economic disadvantage (SED) offer nationwide coverage across standard administrative areas, censuses are performed every 10 years and these indicators are not truly “contextual”. GIS-based measures are often restricted to the assessment of certain macro- and meso-scale features of the physical and built environment, while they are not able to capture either the social or micro-scale features of the community. On the other hand, perception surveys, other than often focusing on specific characteristics, such as the walkability in a community, are subjective in nature and prone to social desirability or other biases. Systematic Social Observations (SSO) is a methodology that enables the assessment of the micro-scale environment objectively via field auditing. SSO can provide useful supplementary information about the micro-scale neighbourhood environment, not captured by other assessment methods and, hence, the identification of environmental inequities which might impact health. Therefore, there is a need for valid audit tools, independent of residents’ perceptions, for profiling the health-related neighbourhood environment. This study explored the feasibility of neighbourhood audits for the first-time in the city of Limassol, Cyprus (population size, 2021 census: 258.900) by developing and field testing a Neighbourhood Observational Tool for the Cypriot urban community environment (CyNOTes). While similar studies commonly explore aspects of reliability of measurement, such as inter- and intra-rater agreement, this study assessed the performance of the audit tool while also employing an iterative multi-validation process for assessing several metric properties of the tool.
Keywords: systematic social observation; neighborhood environment; micro-scale features; community assessmentC; social gradient; audit; perception survey; environmental inequity; συστηματική κοινωνική παρατήρηση; περιβάλλον της γειτονιάς; μικρό-περιβάλλον; αξιολόγηση κοινότητας; κοινωνική διαβάθμιση; επιτόπια επιθεώρηση; έρευνα αντιλήψεων; περιβαλλοντική αδικία; κοινωνικο-περιβαλλοντική ανισότητα